Utilization of novel bacteriocin synthesized silver nanoparticles (AgNPs) for their application in antimicrobial packaging for preservation of tomato fruit - Sharma, Shakshi; Sharma, Nivedita; Kaushal, Neha (Frontiers in Sustainable Food Systems, 2023)
Introduction The current need of the food industry is to develop a safe packaging system that maintains the quality of food and prevents its spoilage. Food safety techniques improvised using functional nanoparticles minimize the chances of spoilage by maintaining moisture stability, mechanical strength, and durability and ensuring product safety. In the present study, we synthesized silver nanoparticles using purified bacteriocins obtained from probiotics. Bacteriocin-synthesized AgNPs are eco-friendly and secure packaging solutions that can be utilized in the packaging industry for the storage of food products. Methods Crude, partially purified and purified bacteriocin was obtained from three potential probiotic isolates, i.e., Lactobacillus pentosus S6 (KU92122), Lactobacillus crustorum F11 (KT865221) and Lactobacillus spicheri G2 (JX481912). The antimicrobial efficacy of bacteriocin was tested against two food-borne spoilage-causing pathogens, i.e., Bacillus cereus and Staphylococcus aureus. The purified bacteriocin obtained was used for the synthesis of AgNPs. The synthesized AgNPs were characterized using UV-vis spectroscopy, TEM, and SEM techniques. The AgNPs were used for coating cellulose paper. The coated paper was characterized using SEM and was used for the storage of tomato fruit. Results and discussion The purified bacteriocin obtained was used for the synthesis of AgNPs. The formation of AgNPs was confirmed by using UV-vis spectroscopy, which showed maximum absorption at 450 nm. Furthermore, we confirm shape and morphology by using Scanning Electron Microscopy (SEM). Transmission Electron Microscopy (TEM) analysis showed the mean size of synthesized AgNPs in the range of 5–20 nm. Bacteriocin-synthesized AgNPs were then used for the coating of cellulose paper with the main motive to avoid spoilage and enhance the shelf stability of tomato fruit during storage. SEM analysis confirmed the coating of AgNPs in the cellulose paper. The enhanced antimicrobial efficacy of different treatments coated paper was observed against B. cereus and S. aureus. Out of all, F11 AgNPs coated paper showed maximum inhibition of 24 mm for S. aureus and 22 mm for B. cereus. The coated paper from three different bacteriocin-synthesized AgNPs, along with silver nitrate (AgNO3) coated and uncoated paper, was used for the storage of tomato fruit for a period of 10 days at room temperature. Changes during storage were determined by analyzing morphological and color changes. Compared to AgNO3 coated and uncoated paper, tomato fruit preserved in F11 AgNPs coated paper maintained and held its appearance and firmness, thereby confirming their effectiveness in the preservation of tomatoes.